Pendidikan Karakter ala Gus Dur: Representasi Pesantren dalam Mendidik Bangsa - M Sofyan Alnashr (SHAHIH: Journal of Islamicate Multidisciplinary, 2019)
This study aims to determine Gus Dur's views on boarding schools as a representation of local wisdom-based character education. This research is qualitative research with the library research method. The analysis technique used is content analysis with a method of interpreting the meaning of an idea contained in Gus Dur's work. The results showed Gus Dur had a concept of character education that emphasized morality in the implementation of education. Character education in question is character education based on local wisdom. Islamic boarding schools are a representation of character education based on local wisdom. Islamic boarding schools teach their students to truly respect the traditions that have developed in the community with the foundation of Islamic teachings. The teachings of Islam and local traditions are used as moral grounds in the real life of people's lives. According to Gus Dur, building character from the door of education must be done comprehensively-integrally, not only through formal education but also through informal and non-formal education.